PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SD STRADA CABANG BEKASI - Puspitaningtyas, Maria Vianney Wahyu; Fathorrahman, Fathorrahman; Pradiani, Theresia (Smart Education, 2024)
Teacher’s performance is a critical factor in achieving the educational goals of institutions. Effective human resources, including leaders and teachers, are essential in task implementation and supervision, ensuring the institution's objectives are met. Perkumpulan Strada strives to foster an excellent, caring, and service-oriented educational community. The role of teachers significantly impacts the quality of students' education. This study aims to investigate the impact of work’s discipline, work’s motivation, and work’s environment on the elementary teachers’ performance at Strada Bekasi Branch partially and simultaneously. This research used multiple linear regression analysis and SPSS 29 software. The sampling method used is saturated sampling, with the entire population of 122 teachers at Strada Bekasi Branch as the sample. Data was collected through an online questionnaire. The findings revealed that work’s discipline does not significantly affect elementary teachers’ performance at Strada Bekasi Branch. However, both work’s motivation and work’s environment have partially and simultaneously a positive and significant impact on elementary teachers’ performance at Strada Bekasi Branch. Keyword: Work’s Discipline, Work’s Motivation, Work’s Environment and Teachers’ Performance